Environmental Scanning on Competitive Advantage in Small Medium Enterprises: The Role of Innovation - Putra, Rahmat Eka; Amali Rivai, Harif (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
Innovation is the main key in achieving competitive advantage in business. Due to the dynamic business environment, small and medium enterprises (SMEs) must prioritize innovation to sustain their competitive advantage. This report offers a comprehensive perspective on how SMEs may effectively cope with any changes and sustain their competitive advantage through innovation. Therefore, explaining the main predictors of innovation in achieving competitive advantage in a dynamic environment is important to do. Through organizational information processing theory (OIPT), this study proposes environmental scanning as the main predictors in explaining innovative performance which in turn has an impact on competitive advantage. Data were collected from 245 SMEs in Indonesia from various industries. Testing the proposed hypothesis of the research was assessed with SEM by assisting Amos software. The results indicated that environmental scanning positively influence competitive advantage. Further the findings were also supported that innovative performance significantly mediates this relationship. This is a cross-sectional research study with a non-probability random sampling method, and self-report questionnaires, therefore possible bias may occur in the research findings. Implications of the research were also discussed in this paper.